Bone Marrow Culture-Derived Conditioned Medium Recovers Endothelial Function of Vascular Grafts following In Vitro Ischemia/Reperfusion Injury in Diabetic Rats - Sevil Korkmaz-Icöz; Gianluca Sistori; Sivakkanan Loganathan; Alex Ali Sayour; Paige Brlecic; Tamás Radovits; Maik Brune; Matthias Karck; Gábor Szabó (Stem Cells International)
Ischemia/reperfusion injury (IRI) remains a challenge in coronary artery bypass grafting (CABG). Diabetic patients with coronary artery disease are more likely to require CABG and therefore run a high risk for cardiovascular complications. Conditioned medium (CM) from bone marrow-derived mesenchymal stem cells has been shown to have beneficial effects against IRI. We hypothesized that adding CM to physiological saline protects vascular grafts from IRI in diabetic rats. Bone-marrow derived cells were isolated from nondiabetic rat femurs/tibias, and CM was generated. As we previously reported, CM contains 23 factors involved in inflammation, oxidative stress, and apoptosis. DM was induced by streptozotocin administration. Eight weeks later, to measure vascular function, aortic rings were isolated and mounted in organ bath chambers (DM group) or stored in 4°C saline, supplemented either with a vehicle (DM-IR group) or CM (DM-IR+CM group). Although DM was associated with structural changes compared to controls, there were no functional alterations. However, compared to the DM group, in the DM-IR aortas, impaired maximum endothelium-dependent vasorelaxation in response to acetylcholine (DM 86.7±0.1% vs. DM-IR 42.5±2.5% vs. DM-IR+CM 61.9±2.0%, p<0.05) was improved, caspase-3, caspase-8, caspase-9, and caspase-12 immunoreactivity was decreased, and DNA strand breakage, detected by the TUNEL assay, was reduced by CM. We present the experimental finding that the preservation of vascular grafts with CM prevents endothelial dysfunction after IRI in diabetic rats. Targeting apoptosis by CM may contribute to its protective effect.